2007
DOI: 10.1002/ep.10187
|View full text |Cite
|
Sign up to set email alerts
|

A study of copper recovery from copper‐contaminated sludge with ferrite and selective leaching processes

Abstract: The purpose of this study was to develop an effective resource recovery and leached residue stabilization process for copper-contaminated sludge. To this end, a treatment procedure utilizing ferrite and selective leaching processes was developed. The XRD examination of ferrite complex revealed the crystalline phases to be mainly Fe 3 O 4 , CuO, and 6CuOÁCu 2 O.A selective leaching process was followed to recover the copper content of the ferrite complex. To promote the dissolution percentage of copper and repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…For example, Hu et al [5] reported copper recovery from copper-contaminated sludge via utilizing ferrite and selective leaching processes. Kuchar et al [6] used a sulfidation treatment process for copper recovery from copper-containing plating sludge.…”
Section: Introductionmentioning
confidence: 98%
“…For example, Hu et al [5] reported copper recovery from copper-contaminated sludge via utilizing ferrite and selective leaching processes. Kuchar et al [6] used a sulfidation treatment process for copper recovery from copper-containing plating sludge.…”
Section: Introductionmentioning
confidence: 98%
“…Since the particle size of hydroxide compounds is very tiny, polyvalent metal ions (i.e., Fe 21 , Fe 31 , Al 31 ) are utilized to form polynuclear-hydrolyzed complexes to promote the settling of the suspension. However, hydrated flocs usually have a high-specific surface area, resulting in water molecules being easily adsorbed on particle surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to wastewater treatments in most plants relying on neutralization precipitation and coagulation, the resultant sludge is composed of metal hydroxides, which are precursors to ferrite formation in our mineralization treatment [21]. The crystalline structure of ferrite is the same as that of the cubic spinel (MgAl 2 O 4 ); however, the positions of Mg 21 and Al 31 are replaced easily by those of M 21 (bivalent metal ions) and Fe 31 . Copper sulfate and ferrous/ferric exist in wastewater systems because ferrous or ferric reagent is used for coagulation during wastewater treatment.…”
mentioning
confidence: 99%
See 2 more Smart Citations